(untitled) - Peter Hobbs (New York, 2000)
This book offers advice on the key skills required by the successful project manager - effective planning, goal and objective setting, scheduling, time management, progress monitoring, and the control of quality and output.
Keywords: industrial management - evaluation,industrial project management